Systems-aware social accountability: Harnessing Practitioner Insights for More Responsive Governance - Guerzovich, Florencia (Pact, 2023)
The framework’s four principles, described below, are not exclusive to social accountability interventions; for example, Pact has published tools on how to use political economy analysis or integrate adaptive management principles into programming. Rather, the principles highlight how – by including the right combination of mindsets, management approaches, analytic approaches and tools – practitioners can develop and apply a deep understanding of a system to improve relationships within it, in support of greater accountability and improved service delivery. - Use a Holistic Lens - Recognize that there is always a system; understand and engage with it​: Developing a strong understanding of the system in which a project works and effectively integrating this knowledge into implementation increases the chances that local actors will sustain the interventions. - Right Fit the Approach​ - Equipped with a holistic understanding of the context, teams identify where they have a comparative advantage in a specific system. In other words, they identify where their resources, expertise and partners have the greatest potential for impact, then set realistic targets that they revise periodically. -Orchestrate Across The System -​ Practitioners take a networked, rather than a top-down, approach to capitalize on their convening power and maximize opportunity to facilitate the most-promising alignments across and within their projects, portfolios and systems. Orchestrators use their individual power, relationships and insight into the local system to enable, not impose, promising interactions and mitigate the risks of damaging ones. - Manage Adaptively - Monitor, evaluate and reflect on emerging patterns of data, evidence and learning to inform decision-making within and, equally importantly, across project cycles. Where possible, practitioners should consider how to use short-term projects to play a long-term game by linking new projects to the lessons and results of their predecessors and ensuring that they are responsive to the evolving context, particularly opportunities, limits and risks.

Anatomy of Social Accountability 3.0: A working framework for moving forward - Guerzovich, Florencia; Aston, Tom (Florianopolis, SC, Brazil: Grupo Politeia, ESAG, University of the State of Santa Catarina and act4delivery, 2023)
This note presents the key components of a potential next generation of social accountability programming. The key aspects outlined emerge from a review of over 150 cases as well as tacit knowledge from dozens of practitioners (Guerzovich and Aston, 2023).The main thread of social accountability 3.0 and what distinguishes it from previous generations is a focus on its contribution towards more responsive systems and accountable social contracts. In particular, social accountability should be considered as an operational means to rework social contracts.Over the last two decades, the field has been defined by a supposed dichotomy between minimalist (i.e., “widget” based) approach or a maximalist (“go big or go home”) approaches. Yet, most practice sits somewhere between these extremes. The paper presents various options derived from practice; practitioners should choose whichever best fits their own particular circumstances.Those hoping to improve and expand their practice with a systems-lens may benefit from considering how they approach the key elements of social accountability 3.0.
Keywords: accountability; development; responsiveness; social accountability; social contract; systems

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.